Interferometric Instrumentation. Issue 69 (10th September 2015) - Berger, J.-P.
Abstract : We present in this chapter a description of optical interferometry combining instruments. For that purpose we describe the role of different key functions and give examples of the choice made in current and future instruments in particular at VLTI.